ANALISIS MANAJEMEN RISIKO PERUSAHAAN (ENTERPRISE RISK MANAGEMENT) DAN KEPATUHAN (COMPLIANCE) TERHADAP KINERJA PERUSAHAAAN - Bambang Sudaryono (Media Riset Bisnis & Manajemen, 2012)
Research on the seven subsidiaries of State Owned Enterprises aims to obtain empirical evidence on enterprise risk management and compliance to corporate performance on audit reporting. The results that enterprise risk management is not significant influence on corporate performance. But compliance has a significant impact on corporate performance. The influence of enterprise risk management and compliance to company performance simultaneously having a more significant contribution than just relying on mere compliance. The impact of this research on internal audit theory that the corporation should include aspects of the risk management as has been adopted in the COSO 2004.Keywords: Enterprise risk management, Compliance, Corporate performance